3D Microfluidic Bone Tumor Microenvironment Comprised of Hydroxyapatite/Fibrin Composite - Ahn, Jungho; Lim, Jungeun; Jusoh, Norhana; Lee, Jungseub; Park, Tae-Eun; Kim, YongTae; Kim, Jangho; Jeon, Noo Li (Frontiers in Bioengineering and Biotechnology, 2019)
Bone is one of the most common sites of cancer metastasis, as its fertile microenvironment attracts tumor cells. The unique mechanical properties of bone extracellular matrix (ECM), mainly composed of hydroxyapatite(HA) affect a number of cellular responses in the tumor microenvironment (TME) such as proliferation, migration, viability, and morphology, as well as angiogenic activity, which is related to bone metastasis. In this study, we engineered a bone-mimetic microenvironment to investigate the interactions between the TME and HA using a microfluidic platform designed for culturing tumor cells in 3D bone-mimetic composite of HA and fibrin. We developed a bone metastasis TME model from colorectal cancer (SW620) and gastric cancer (MKN74) cells, which has very poor prognosis but rarely been investigated. The microfluidic platform enabled straightforward formation of 3D TME composed the hydrogel and multiple cell types. This facilitated monitoring of the effect of HA concentration and culture time on the TME. We analyzed the effect of bone mineral components on the viability, proliferation, morphology, and migration of tumor cells in the HA/fibrin composite. In addition, the platform allowed direct observation of angiogenesis induced by tumor cells and fibroblasts embedded in the HA/fibrin matrix. Moreover, vascularized tumor-stromal spheroids were reconstituted to recapitulate the TME. The results demonstrate that the microfluidic platform facilitates investigation of the responses of cancer cells in a bone mimicking microenvironment composing a tunable HA/fibrin composite. Our approach could be applied to drug screening and mechanistic studies of the metastasis, growth, and progression of metastatic bone TME.